Towards a motivational model of flow. - Kowal, John. (University of Ottawa (Canada), 1998)
The purpose of this thesis was to examine the relationship between motivation and flow. As a conceptual framework for investigating motivation, Vallerand's (1997) Hierarchical Model of Intrinsic and Extrinsic Motivation (HMIEM) which is based predominantly on Deci and Ryan's Self-Determination Theory (Deci & Ryan, 1985, 1991) was used. The work of Csikszentmihalyi (1975a, 1991) served as a theoretical basis for examining the flow state. Canadian master's level swimmers completed questionnaires on two separate occasions, Time 1 $(n = 203)$ and Time 2 $(n = 104).$ At Time 1, situational measures of distal motivational determinants (perceptions of success and perceptions of the motivational climate), proximal motivational determinants (perceptions of autonomy, perceptions of competence, and perceptions of relatedness), self-determined motivation, and flow were assessed immediately following a swim practice. Contextual measures of these same variables were assessed at Time 2 (one week later) with the exception of flow. Two sets of analyses were then conducted in order to examine the links between these motivational concepts and flow. (Abstract shortened by UMI.)
Keywords: Psychology, Social.